Analisis Faktor-Faktor yang Mempengaruhi Pengelolaan Keuangan Pribadi Mahasiswa - Hikmayani Subur; Septiannisa Paramita (Indo Publishing, 2025)
This study aims to analyze the factors influencing personal financial management among students at the Faculty of Economics and Business, Makassar State University. Using a descriptive qualitative approach, data were collected through in-depth interviews, non-participatory observation, and documentation from 12 purposively selected informants. Thematic analysis revealed five main factors influencing students' financial behavior: financial literacy, a consumptive lifestyle, limited income, social influences, and mindsets about money. Although students have a basic understanding of financial concepts such as recording expenses and budgeting, their application is often hampered by a lack of discipline, social pressure, and consumptive habits influenced by digital media and peer groups. Limited income also hinders the ability to plan long-term finances, leading some students to experience financial stress and unstable financial behavior. Furthermore, mindsets about money have been shown to shape students' financial decisions, with a positive mindset increasing the likelihood of wiser financial behavior. These findings emphasize the importance of applicable financial literacy education, strengthening self-control, and developing a healthy financial mindset to improve the quality of students' personal financial management.